Stem cell microencapsulation maintains stemness in inflammatory microenvironment - Yajun Zhao; Yilin Shi; Huiqi Yang; Mengmeng Liu; Lanbo Shen; Shengben Zhang; Yue Liu; Jie Zhu; Jing Lan; Jianhua Li; Shaohua Ge (Nature Publishing Group, 2022)
Abstract Maintaining the stemness of the transplanted stem cell spheroids in an inflammatory microenvironment is challenging but important in regenerative medicine. Direct delivery of stem cells to repair periodontal defects may yield suboptimal effects due to the complexity of the periodontal inflammatory environment. Herein, stem cell spheroid is encapsulated by interfacial assembly of metal-phenolic network (MPN) nanofilm to form a stem cell microsphere capsule. Specifically, periodontal ligament stem cells (PDLSCs) spheroid was coated with FeIII/tannic acid coordination network to obtain spheroid@[FeIII-TA] microcapsules. The formed biodegradable MPN biointerface acted as a cytoprotective barrier and exhibited antioxidative, antibacterial and anti-inflammatory activities, effectively remodeling the inflammatory microenvironment and maintaining the stemness of PDLSCs. The stem cell microencapsulation proposed in this study can be applied to multiple stem cells with various functional metal ion/polyphenol coordination, providing a simple yet efficient delivery strategy for stem cell stemness maintenance in an inflammatory environment toward a better therapeutic outcome.